Identificación de líneas espectrales atómicas características de oro, plata y cobre mediante la técnica LIBS - Camacho Chávez, Robin Noé (2022)
The present work was born from the need for experimental techniques for the_x000D_ multi-elemental analysis of archaeological objects from the northern region of Peru,_x000D_ which is of great help for the characterization of such objects that are part of the_x000D_ cultural heritage of the nation, being the laser induced plasma spectroscopy (LIBS) a_x000D_ good alternative to meet this need. The main objective of the present work was to set_x000D_ up a system for laser induced plasma spectroscopy based on a minispectrometer, a_x000D_ 1064nm Nd:YAG IR laser and accessories, which was tested with metallic samples of_x000D_ gold, silver and copper of high purity. This system was able to direct the laser_x000D_ radiation on the surface of the samples, producing the ablation of the irradiated_x000D_ material with the corresponding plasma generation. The photons emitted by the_x000D_ plasma were in turn directed by an optical system to the mini spectrometer for_x000D_ recording and subsequent analysis, and finally a qualitative analysis protocol was_x000D_ established based on algorithms built in Python to subtract and normalize the_x000D_ spectra. The results obtained were encouraging, obtaining the main characteristic_x000D_ spectral lines for silver, gold and copper, such as: 267nm, 328nm, 338nm for silver,_x000D_ 389nm, 406nm, 479nm, 523nm, 587nm for gold and 466nm, 510nm, 515nm, 521nm,_x000D_ 530nm, 577nm for copper